Kekuasaan dan Hak Asasi Manusia (Kajian Filosofis terhadap Pemikiran Raja Ali Kelana) - abd rahman mawazi (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
This paper aims to find out about Raja Ali Kelana's thoughts on power and human rights. This study focuses on his work entitled Kitab Kumpulan Ringkas Berbetulan Lekas (KRBL). In this study, it is known that Raja Ali Kelana has thoughts about fiqh al-siyasah or politics contained in this KRBL. He reviews how the structure of power, its usefulness and who deserves to be the ruler. From this study it is known that the purpose of power is to protect religion and the welfare of the people. In the right to protect the people, King Ali Kelana requires every leader to be friendly to the people and listen to the aspirations of his people. A prosperous people is a people whose basic rights are fulfilled. Therefore, fulfilling the rights of the people is an important part of the existence of a state. Some of the basic rights of the people are the right to loyalty, the right to life, the right to freedom, the right to get a decent life. This means that some rights are related to the self and some are related to property. From Raja Ali Kelana's thoughts, at least it needs to be a common consideration and study regarding the importance of strengthening the fulfillment of human rights by every ruler. Instead of making power to deprive the people of their rights.